2021
DOI: 10.3390/jpm11121338
|View full text |Cite
|
Sign up to set email alerts
|

Psoas Muscle Volume as an Opportunistic Diagnostic Tool to Assess Sarcopenia in Patients with Hip Fractures: A Retrospective Cohort Study

Abstract: Purpose: This study aims to determine whether the psoas volume measured from a pelvic computed tomography (CT) could be a potential opportunistic diagnostic tool to measure muscle mass and sarcopenia in patients with hip fractures. Methods: This was a retrospective cohort study. In total; 57 consecutive patients diagnosed with hip fractures who underwent surgery were enrolled. A cross-sectional area of the psoas muscle was measured at the lumbar (L) 3 and L4 vertebrae from a pelvic CT for the diagnosis of hip … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In CRC, there are reports on use of PV and PA for post-chemoradiotherapy rectal cancer and postoperative complications [22][23][24][25][26], but we could not nd any studies on long-term prognosis and 5-year survival rate in elderly patients with CRC. In this regard, our study is novel in addressing these perspectives.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In CRC, there are reports on use of PV and PA for post-chemoradiotherapy rectal cancer and postoperative complications [22][23][24][25][26], but we could not nd any studies on long-term prognosis and 5-year survival rate in elderly patients with CRC. In this regard, our study is novel in addressing these perspectives.…”
Section: Discussionmentioning
confidence: 91%
“…In PA measurement, the measured height may not correspond to the maximum area, and signi cant variations can occur depending on the level of measurement [23,24]. So et al argued that 3D assessments in patients with hip fractures are more accurate for evaluating muscle mass compared to 2D methods [25]. On the other hand, one report suggested that both PA and PV are effective [26].…”
Section: Discussionmentioning
confidence: 99%
“…However, psoas muscle is originated from T12 and inserted to femur. Scanning from chest to lower limbs is required for the exact evaluation of psoas muscle and muscle mass at the mid-level of psoas muscle, taken from abdominal scanning, has been used in the previous studies ( 17 , 18 ). Additionally, scanning increased the risk for the exposure of biohazard.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, given the improvement of technology, three-dimensional psoas muscle volume has been proposed as an alternative to the above conventional index. The psoas muscle volume is strongly correlated with the cross-sectional total muscle area at the horizontal height of L3, and its decrease with age, as with dual-energy X-ray absorptiometry and bioelectrical impedance analysis muscle mass measurements, has also been observed [ 19 ].…”
Section: Discussionmentioning
confidence: 99%